2017
DOI: 10.1016/j.jtusci.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the nonlinear equation of the circular sector oscillator by Akbari-Ganji’s method

Abstract: In this paper, a new and innovative semi-analytical method called Akbari-Ganji's method (AGM) has been applied to solve nonlinear equations of the semicircular oscillator. The major concern is to achieve an accurate solution that has an efficient approximation according to the Runge-Kutta numerical method. The results are presented for different values of parameters to demonstrate the applicability of this method. It was found that the proposed solution is very accurate and efficient for the discussed problem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Most of the established models are semiempirical formulas, which have certain errors and are not universal. Although the semianalytical solution methods such as AGM (Akbari-Ganji's method) [33][34][35] and HAM (homotopy analysis method) [36] can directly obtain more accurate linear or nonlinear solutions, the difficulty of its application is relatively large, which is not conducive in solving practical engineering problems. Numerical simulations can clearly present the flow conditions inside the separator, and most of the physical models proposed by the current research are not perfect due to the lack of an overall description of the relevant characteristics of the separator.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the established models are semiempirical formulas, which have certain errors and are not universal. Although the semianalytical solution methods such as AGM (Akbari-Ganji's method) [33][34][35] and HAM (homotopy analysis method) [36] can directly obtain more accurate linear or nonlinear solutions, the difficulty of its application is relatively large, which is not conducive in solving practical engineering problems. Numerical simulations can clearly present the flow conditions inside the separator, and most of the physical models proposed by the current research are not perfect due to the lack of an overall description of the relevant characteristics of the separator.…”
Section: Introductionmentioning
confidence: 99%
“…They found that thermal conductivity improved with the increment of volume fraction and temperature. Heat transfer of nanofluid flow was analyzed by Ganji and coworkers, 13–15 and they found that under the influence of Lorentz force, the removal of heat from the nanofluid flow was high. Sahid et al 16 experimentally proved that TiO2ZnOEG–water hybrid nanofluid has stability and enhanced thermal conductivity due to suspended nanoparticles and the base fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear vibration of the system is mainly divided into weakly nonlinear oscillations and strong nonlinear vibration. The semi-analytical method (Akbari et al., 2017; Mirgolbabaee et al., 2017) and numerical analysis method are also used to solve the nonlinear vibration model.…”
Section: Introductionmentioning
confidence: 99%